PENGELOLAAN PENDIDIKAN KARAKTER SISWA BERBASIS KECERDASAN EMOSIONAL DAN SPRITUAL DI SMP NEGERI SE-KECAMATAN TILAMUTA - Frista Iin Wahyuni (LP2M Universitas Bina Mandiri Gorontalo, 2018)
The purpose of this research is to find out the emotional intelligence coaching in State Junior High Schools in Tilamuta Subdistrict, knowing the spiritual intelligence coaching in State Junior High Schools in Tilamuta subdistrict. The method of the research is a quantitative explanatory approach. The method of collecting data used observation, questionnaire and interview guidelines. The results of the research show that the formation of students' emotional intelligence includes implementation, monitoring, and evaluation. The implementation of the training of students' emotional intelligence in-state junior high schools of Tilamuta subdistrict includes the formation of personal skills and social skills. In the implementation of the personal skills values, social skills in the state junior high schools of Tilamuta subdistrict are in a good category. Furthermore, monitoring activities are carried out through the establishment of accrual ability scores, ability to access levels of thinking, the ability to understand emotions, and ability to promote emotions. Tilamuta subdistrict includes the formation of personal skills and social skills. The activity of monitoring the establishment of accrual ability scores, the ability to access the level of thinking, the ability to understand emotions, the ability to promote emotion in the state junior high schools in Tilamuta Subdistrict are in a good category. For evaluation activities, it is carried out through fostering students' self-confidence and solidarity assessment and the results of evaluations carried out are in a good category. The development of students' spiritual intelligence includes implementation, monitoring and evaluation. The implementation activities of students' spiritual intelligence development in state Junior high schools of Tilamuta Subdistrict included the formation of values. The implementation of spiritual intelligence development included the formation of students' creative values. In the implementation of students' creative values, in-state junior high schools in Tilamuta subdistrict are in a good category. Furthermore, monitoring activities are carried out through fostering students' independence values. Monitoring activities for the formation of students' self-reliance values in state junior high school in Tilamuta subdistrict are in a good category. For evaluation activities carried out through coaching time utilization for students and assessment of time utilization for students. From the results of the evaluation, the whole groups are in a good category